2019
DOI: 10.3390/geosciences9080328
|View full text |Cite
|
Sign up to set email alerts
|

Frost Resilience of Stabilized Earth Building Materials

Abstract: Earth-based building materials are increasingly valued in green design for their low embodied energy, humidity-buffering ability, and thermal stability. These materials perform well in warm dry climates, but greater understanding of long-term durability is needed for successful adoption in colder and/or wetter climates. The presence of stabilizers dramatically improves resistance to surface erosion from wind and rain, compared to unstabilized adobe and cob counterparts, and the influences of soil composition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 106 publications
0
14
0
Order By: Relevance
“…As the lime and rice husk ratio increased the water absorption rate decreased significantly from 9.60% to 0.80%. However, water absorption properties of all lime and rick husk blended specimens met the Indonesian Standard SNI 15-2094-2000 [18] for masonry brick.…”
Section: Bottom Ashmentioning
confidence: 92%
See 1 more Smart Citation
“…As the lime and rice husk ratio increased the water absorption rate decreased significantly from 9.60% to 0.80%. However, water absorption properties of all lime and rick husk blended specimens met the Indonesian Standard SNI 15-2094-2000 [18] for masonry brick.…”
Section: Bottom Ashmentioning
confidence: 92%
“…However, some of the disadvantages of earth construction are the lack of strength, durability and vulnerability to erosion by rain [13][14][15]. Unfortunately, due to these drawbacks, the use of earth building materials in the modern construction sector has been ignored over many years [16] and is being extensively replaced by more durable and stronger construction materials such as fired brick and concrete [14,17,18]. However, unfired earth masonry provides many advantages compared to traditional fired brick and concrete masonry in terms of environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…We simplify our treatment of ground temperatures by neglecting the effects of latent heat when approximating the temperature profiles. While damage is reduced under unsaturated conditions, whereas damage is enhanced by the high temperature gradients that accompany increased radiative transfer (Rempel & Rempel, 2019), we make no attempt to take such factors into account. Our focus on gauging regional variations in damage over annual cycles motivates our simplified approach in approximating surface temperatures with the output of the paleoclimate simulations described below, and assuming the conditions necessary for full saturation throughout.…”
Section: Methodsmentioning
confidence: 99%
“…Cement CEM I 42.5 R (Table 3) was added to these mixtures, in the amount of 6% and 9% by mass of the remaining dry ingredients. These values were chosen based on the authors' own previous study, which found that 6% cement ensured an adequate compressive strength for the CSRE [3,5,30], while 9% cement was needed in regards to durability [33][34][35][36][37]. To the 14 soil-cement mixtures (Table 4) that were obtained in this way, water was added, ensuring that the optimum moisture content (OMC) of the mixture was achieved, i.e., the moisture at which compaction by ramming achieved the maximum value of dry density (the method of determining the OMC is given in Section 2.2.2).…”
Section: Methodsmentioning
confidence: 99%